Pengaruh massage payudara, teknik menyusui terhadap risiko terjadinya mastitis - Hanifah Sofi Maharani; Fatimah Sari; Etika Desi Yogi; Arita Muwarni; Juda Julia (Health Sciences and Pharmacy Journal, 2023)
Breastfeeding technique is the most important factor compared to other risk factors that can increase the risk of mastitis. Proper breastfeeding position and attachment of the baby to the mother's breast in breastfeeding techniques will reduce the possibility of problems in the breastfeeding process such as mastitis. One of the efforts that can be made to reduce the risk of mastitis in breastfeeding mothers is breast massage. Breast massage or also known as breast care is a technique performed by health workers to increase breast milk production. In addition, breast massage can reduce the strong tension in the mother's breast muscles, so that it can encourage relaxation and relieve pain. The study used an analytic survey method using a cross sectional approach with accidental sampling technique and obtained 17 nursing mothers as research samples. Data collection was done using observation sheets and questionnaires. The results of hypothesis testing using the Chi Square test showed that there was an influence between breastfeeding techniques and breast massage on the risk of mastitis in breastfeeding mothers at PMB Ponorogo Regency. Breastfeeding mothers who are given breast massage therapy and have proper breastfeeding techniques are proven to be able to reduce the risk of mastitis.